PROBLEMATIKA PENEGAKAN PERATURAN DAERAH TENTANG PENYAKIT MASYARAKAT DALAM PENERTIBAN USAHA HIBURAN KARAOKE - Gilbert Johan Martin Sinaga (Jurnal Jendela Hukum, 2026)
This study examines the implementation of Regional Regulation of Kuantan Singingi Regency Number 20 of 2002 on Social Maladies in the enforcement of karaoke entertainment businesses. The research aims to analyze the enforcement practices, identify the obstacles encountered, and examine the efforts undertaken by the local government in implementing the regional regulation. Employing an empirical legal research method with a socio-legal approach, the study draws on interviews and field observations supported by primary and secondary legal materials. The findings indicate that the implementation of the regional regulation has not been substantively effective, despite its clear normative legal basis. The lack of firmness in the application of sanctions, weak coordination among law enforcement agencies, and inadequate socialization to business operators and the public constitute the main factors undermining enforcement effectiveness. This study underscores that the effectiveness of regional regulations is highly dependent on the consistency of law enforcement, institutional capacity, and the level of societal support.